CFD Analysis on the Effects of Various Train Lengths on Aerodynamic Loads and Flow Structure for Train Travelling Through Various Crosswind Conditions - Lai Swee Yong; Ishak, Izuan Amin; Mohammad Arafat; Nurnida Elmira Othman; Nur Haziqah Shaharuddin; Nurshafinaz Mohd Maruai (Journal of Advanced Mechanical Engineering Applications, 2025)
To ensure that railroad vehicles operate safely in crosswind conditions, it is essential to take into account the aerodynamic contribution of train length. As a result, this study aims to investigate the effect of different lengths of the Next-Generation High-Speed Trains (NG-HST) model when traveling under various crosswind conditions in terms of aerodynamic loads and flow structure formation with a Computational Fluid Dynamics (CFD) technique known as Reynold-Averaged Navier Stokes (RANS) combined with the k-epsilon (k??) turbulence model. Based on the train model’s height and speed, the Reynolds number used is 1.3 x 106. The two aerodynamic performance characteristics, aerodynamic loads and flow structure formation, were analyzed using different train lengths: Case 1 (1 middle coach), Case 2 (3 middle coaches), and Case 3 (5 middle coaches) and varied crosswind yaw angles: 0°, 15°, 30°, 45°, and 60°. The findings indicate that as the crosswind yaw angle and train model’s length increase, more flow comes into contact with the train model’s surface on the windward side, resulting in a huge area of the high-pressure region and low-pressure region on the windward and leeward sides, respectively. In addition, the side force coefficient increases for the 60° crosswind yaw angle by about 12% for Case 3 (train with 5 middle coaches) compared to Case 1 (1 middle coach). Therefore, it can be concluded that the longer the train, the more pronounced the aerodynamic forces under high crosswind conditions, which may negatively impact stability and operational safety.